(untitled) (LEARNing Landscapes, 2009)
The science curriculum reform by Quebec’s Ministère de l’Éducation, du Loisir et du Sport (MELS) mandates the use and evaluates the performance of students in activities that would be defined as inquiry-based. This article discusses the importance of using inquiry-based laboratory experiments and assesses the challenges that teachers face when using this type of pedagogy.